Clinical importance and representation of toxigenic and non-toxigenic Clostridium difficile cultivated from stool samples of hospitalized patients - Stojanovic,Predrag (2012)
The aim of this study was to fortify the clinical importance and representation of toxigenic and non-toxigenic Clostridium difficile isolated from stool samples of hospitalized patients. This survey included 80 hospitalized patients with diarrhea and positive findings of Clostridium difficile in stool samples, and 100 hospitalized patients with formed stool as a control group. Bacteriological examination of a stool samples was conducted using standard microbiological methods. Stool sample were inoculated directly on nutrient media for bacterial cultivation (blood agar using 5% sheep blood, Endo agar, selective Salmonella Shigella agar, Selenite-F broth, CIN agar and Skirrow's medium), and to selective cycloserine-cefoxitin-fructose agar (CCFA) (Biomedics, Parg qe tehnicologico, Madrid, Spain) for isolation of Clostridium difficile. Clostridium difficile toxin was detected by ELISA-ridascreen Clostridium difficile Toxin A/B (R-Biopharm AG, Germany) and ColorPAC ToxinA test (Becton Dickinson, USA). Examination of stool specimens for the presence of parasites (causing diarrhea) was done using standard methods (conventional microscopy), commercial concentration test Paraprep S Gold kit (Dia Mondial, France) and RIDA®QUICK Cryptosporidium/Giardia Combi test (R-Biopharm AG, Germany). Examination of stool specimens for the presence of fungi (causing diarrhea) was performed by standard methods. All stool samples positive for Clostridium difficile were tested for Rota, Noro, Astro and Adeno viruses by ELISA - ridascreen (R-Biopharm AG, Germany). In this research we isolated 99 Clostridium difficile strains from 116 stool samples of 80 hospitalized patients with diarrhea. The 53 (66.25%) of patients with diarrhea were positive for toxins A and B, one (1.25%) were positive for only toxin B. Non-toxigenic Clostridium difficile isolated from samples of 26 (32.5%) patients. However, other pathogenic microorganisms of intestinal tract cultivated from samples of 16 patients. Examination of cultivated colonies revealed that most of cultivated species belonged to genera of Campylobacter spp., Salmonella spp., and Candida spp.. In control group, toxigenic Clostridium difficile cultivated from stool samples of two patients (2%) and non-toxigenic Clostridium difficile from samples of five patients (5%). This research confirmed clinical importance of toxigenic Clostridium difficile found in liquid stool samples of hospitalized patient, and the possibility of asymptomatic carriage in 2% of patients with formed stool.